THE REFLECTION OF PEDAGOGUE’S IDENTITY IN THE LIFE ACTIVITIES: THEORETICAL RESEARCH MODEL - Medveckis, Arturs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The innovative research model presented in this article includes the micro, mezzo, and macro context of the identity by expressing its multiple dimensions of the pedagogue’s personality in personal, cultural and historical and social aspect.  The dispositional traits of personality i.e. emotions, talent, behaviour and opinion, along with the adaptation characteristics i.e. interests, motivation, values, attitudes and character are analysed in the micro context. The meaning of the respective social environment is drawn in the mezzo context where the pedagogue’s, family, student’s and religious identity develop. The further crystallisation of the identity happens in the macro context that influences the development of professional, national, local, political and cultural identity.